Traditional Knowledge of Stingless Bees (Hymenoptera: Apidae: Meliponini) in the Peruvian Amazon - Delgado, Cesar; Mejía, Kember; Rasmussen, Claus; Romero, Rosa (Ethnobiology Letters, 2023)
This paper describes the traditional knowledge on the management of stingless bee colonies and the use of honey by Indigenous and non-Indigenous communities of the department of Loreto, in the Peruvian Amazon. Semi-structured interviews and collection of voucher bees were carried out from June to August 2016 and from November to December 2017. The informants were selected through intentional non-probabilistic sampling (snowball sampling). During the study, 21 communities were visited, of which some of the community members in thirteen communities kept stingless bees. A total of 17 species of stingless bees are reported as used in the communities for either rearing or harvesting of honey from the forest with Melipona eburnea being the most common species. The way communities classify, manage, and use bees depends on how they perceive these insects, informed by knowledge processed and incorporated from other communities. In these communities, they use honey and pollen, with honey being the main product. Fourteen health conditions are treated with honey, with the most treated conditions being related to respiratory ailments, fertility, and reproduction. The study provides a basis for incorporating stingless bees into conservation and sustainable production policies.